The Relationship Between Postoperative Pain and Sleep Quality in Cesarean Section Patients at Koja Hospital - Tridiyawati, Feva (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Maternal mortality continues to be a pressing global health issue, particularly in low- and middle-income countries. Postpartum complications, including poor sleep quality, can impede maternal recovery and are often exacerbated by unmanaged postoperative pain following cesarean section. Understanding the link between pain and sleep disturbance is critical to enhancing maternal care and recovery outcomes. Objective: This study aimed to examine the correlation between postoperative wound pain and sleep quality among women undergoing cesarean section at Koja District Hospital in 2020. Methods: A cross-sectional study was conducted involving 40 postpartum women who met the inclusion criteria. Participants were selected through total sampling. Pain intensity was measured using a standardized numerical pain rating scale, while sleep quality was assessed using a validated sleep quality questionnaire. Data were analyzed using the Pearson chi-square test to evaluate the relationship between pain severity and sleep quality. Results: The analysis revealed a statistically significant correlation between the intensity of cesarean wound pain and sleep quality (p = 0.001). Women reporting higher levels of postoperative pain were more likely to experience disturbed or poor-quality sleep. Conclusion: A significant relationship exists between postoperative pain and sleep quality in post-cesarean patients. These findings underscore the importance of effective pain management as part of comprehensive postpartum care to improve sleep quality and facilitate optimal recovery. Future studies are recommended to explore longitudinal effects and potential interventions targeting both pain and sleep in the postpartum period.